Determination of vitamin K encapsulated into lipid nanocarriers by dispersive liquid–liquid microextraction combined with liquid chromatography–atmospheric pressure chemical ionization–tandem mass spectrometry. Issue 2 (17th October 2022) - Yoo, Guijae; Kim, Tae‐Eun; Lee, Min Hyeock; Kim, Bum‐Keun; Jang, Hae Won
Abstract: Dispersive liquid–liquid microextraction was used in conjunction with liquid chromatography–atmospheric pressure chemical ionization–tandem mass spectrometry to quantitate vitamins K1 and K2 in vitamin‐fortified emulsions, and vital microextraction parameters were optimized using response surface methodology coupled with Box–Behnken design. Under optimal microextraction conditions, highly linear ( R 2 > .999) calibration curves were obtained for both vitamins in a broad concentration range (1–1000 μg/L), and vitamin recoveries exceeded 90%. The detection and quantitation limits equaled 1.89 and 5.72 μg/L for vitamin K1, respectively, and 5.00 and 15.15 μg/L for vitamin K2, respectively. When applied to vitamin‐K‐loaded nanoemulsions and solid lipid nanoparticles, the developed method achieved excellent results, outperforming the currently employed Korean Food Code method, and therefore holding great promise for the quantitation of vitamin K in vitamin‐fortified food products. Abstract : The proposed method uses dispersive liquid–liquid microextraction (DLLME) in conjunction with liquid chromatography–atmospheric pressure chemical ionization–tandem mass spectrometry (LC‐APCI‐MS/MS) and is optimized using the response surface model (RSM) based on a Box–Behnken design (BBD). The developed method is powerful and reliable, and is a suitable alternative to the current Korean Food Code analytical method.